Impacts of considering climate variability on investment decisions in Ethiopia - Block, Paul J.; Strzepek, Kenneth M.; Rosegrant, Mark W.; Diao, Xinshen (International Food Policy Research Institute, 2006)
Extreme interannual variability of precipitation within Ethiopia is not uncommon, inducing droughts or floods and often creating serious repercussions on agricultural and non-agricultural commodities. An agro-economic model, including mean climate variables, was developed to assess irrigation and road construction investment strategies in comparison to a baseline scenario over a 12-year time horizon. The motivation for this work is to evaluate whether the inclusion of climate variability in the model has a significant effect on prospective investment strategies and the resulting country-wide economy. The mean climate model is transformed into a variable climate model by dynamically adding yearly climate-yield factors, which influence agricultural production levels and linkages to non-agricultural goods. Nine sets of variable climate data are processed by the new model to produce an ensemble of potential economic prediction indicators. Analysis of gross domestic product and poverty rate reveal a significant overestimation of the country’s future welfare by the mean climate model method, in comparison to probability density functions created from the variable climate ensemble. The ensemble is further utilized to demonstrate risk assessment capabilities. The addition of climate variability to the agro-economic model provides a framework, including realistic ranges of economic values, from which Ethiopian planners may make strategic decisions.